INVESTIGATION OF ANNEALING EFFECT ON THE FORWARD BIAS AND LEAKAGE CURRENT CHANGES OF P-TYPE 6H-SIC SCHOTTKY DIODES WITH SIO2 RAMP PROFILE AFTER IRRADIATED UP TO 1.75 MGY (Application For Nuclear Fuel Elements Facilities) - Usman Sudjadi . (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2009)
Abstract Investigation of Annealing Effect on the Forward bias and Leakage current Changes of P-Type 6H-SiC Schottky Diodes with SiO2 Ramp Profile after Irradiated Up to 1.75 MGy. Annealing effect on the electrical properties change of    P-type 6H-SiC Schottky diodes with SiO2 ramp profile after irradiated up to 1.75 MGy at RT (Room Temperature) were investigated.  A perpendicular edge termination based on oxide ramp profile around the Schottky contact is used on Al Schottky rectifier fabricated on a 10 μm p-type 6H-SiC epi-layer on p-type 6H-SiC substrate (3.50 off, Si face), Na: 5.9 x 1015/cm2 .  The samples were irradiated with gamma-ray up to 1.75 MGy after that the samples annealed at 100 0C - 500 0C for 30 minute, respectively. The electrical characteristics of the diodes are evaluated before and after irradiated, before and after irradiated plus annealed.   The results have shown that the forward current increases with increasing annealing temperatur. Keywords: Annealing effect, forwards bias, leakage current, 6H-SiC, Schottky diode Abstrak Efek pemanasan pada perubahan sifat-sifat kelistrikan dari diode – diode Schottky 6H-SiC tipe P dengan SiO2 ramp profile setelah diirradiasi di atas1,75 MGy. efek pemanasan pada perubahan sifat-sifat kelistrikan dari diode – diode Schottky 6H-SiC tipe P dengan SiO2 ramp profile setelah diirradiasi di atas1,75 MGy pada temperatur ruang telah diteliti.  Sebuah terminasi oxide dengan sudut tegak lurus untuk ramp profile di sekeliling kontak Schottky telah digunakan pada Al penyearah Schottky, difabrikasi pada sebuah 10 μm 6H-SiC pada tipe P epi-layer, pada 6H-SiC tipe P substrate (3,50 off, Si face), Na: 5,9 x 1015/cm2.  Cuplikan diirradiasi dengan sinar gamma di atas 1,75 MGy setelah itu cuplikan masing-masing dipanaskan pada suhu 100 0C - 500 0C selama 30 menit.  Karakteristik kelistrikan dari diode-diode dievaluasi sebelum dan sesudah diirradiasi. Dievaluasi juga sebelum dan sesudah diirradiasi dan  dipanaskan.  Hasil-hasilnya menunjukkan bahwa arus maju menaik dengan kenaikan temperatur pemanasan. Kata Kunci: Efek pemanasan, tegangan bias maju, kebocoran arus, 6H-SiC, diode Schottky.